ANALYZING THE EFFECT OF HEALTH AND APPEARANCE CONSCIOUSNESS ON INTENTION TO CALCULATE CALORIE INFORMATION IF DISPLAYED AT FAST FOOD RESTAURANT MENU - Kumalasari, Henny; Sjafei, Netta J. (Journal of Business Strategy and Execution, 2012)
In fast food industry, there are so many challenges due to their non-healthy food images. In Indonesia, in Jakarta particularly, the increase of economic situation have bring up more and more people to better social and economic condition which make them tend to be more concerned with their health and safety of their food. In US, the initiative to display calorie information had begun. However, it is not yet done in Indonesia. Therefore, the purpose of this study is to examine consumer’s intention toward calculating calorie information when they buy fast food based on the Theory of Planned Behavior by Azjen (1985) and also considering consumer values which is health and appearance consciousness as antecedent of Attitude toward the behavior. Total of 146 valid respondents was collected through e-questionnaire. Multiple regression analysis were conducted using SPSS 17.0 and the findings of this research indicating that health and appearance consciousness significantly and positively influence attitude toward calculating calorie information when buying fast food. Moreover, the results revealed that attitude, subjective norm, and perceived behavioral control also significantly and positively influence consumers’ intention toward calculating calorie information when buying fast food. By understanding this study results, fast food industry could develop an effective marketing strategy in order to prepare the healthy lifestyle in urban area such as Jakarta which increase recently and repair the non-healthy food image.